Repetition suppression of face‐selective evoked and induced EEG recorded from human cortex. Issue 8 (22nd February 2014) - Engell, Andrew D.; McCarthy, Gregory
Abstract: In functional MRI studies, repetition suppression refers to the reduction of hemodynamic activation to repeated stimulus presentation. For example, the repeated presentation of a face reduces the hemodynamic response evoked by faces in the fusiform gyrus. The neural events that underlie repetition suppression are not well understood. Indeed, in contrast to the hemodynamic response, the face‐specific N200 recorded from subdural electrodes on the ventral occipitotemporal cortex, primarily along the fusiform gyrus, has been reported to be insensitive to face‐identity repetition. We have previously described a face‐specific broadband gamma (30–100 Hz) response at ventral face‐specific N200 sites that is functionally dissociable from the N200. In this study, we investigate whether gamma and other components of the electroencephalogram spectrum are affected by face‐identity repetition independently of the N200. Participants viewed sequentially presented identical faces. At sites on and around the fusiform gyrus, we found that face repetition modulated alpha (8–12 Hz), low‐gamma (30–60 Hz), and high‐gamma (60–100 Hz) synchrony, but not the N200. These findings provide evidence of a spatially co‐localized progression of face processing. Whereas the N200 reflects an initial obligatory response that is less sensitive to face‐identity repetition, the subsequent spectral fluctuations reflect more elaborative face processing and are thus sensitive to face novelty. It is notable that the observed modulations were different for different frequency bands. We observed repetition suppression of broadband gamma, but repetition enhancement of alpha synchrony. This difference is discussed with regard to an existing model of repetition suppression and behavioral repetition priming. Hum Brain Mapp 35:4155–4162, 2014 . © 2014 Wiley Periodicals, Inc .